The protective effect of Sider honey and Zinc on imidacloprid induced hepatorenal and hematological toxicity in rats - Al-Awar, Mohammed; Gumaih, Hussein; Al-Ameri, Dawlat; Al-Hamdani, Nada; Al-Eriani, Mohammed; Muaqeb, Adel; Moqbel, Fahmi (Journal of natural sciences, life and applied sciences, 2018)
The present study aimed at evaluating the ability of antioxidants S.honey and Zn (2doses; high and low) for 30 days to ameliorate alterations caused by imidacloprid (IM) insecticide in damaged hepatorenal and hematological of rats. Rats oral administration with IM caused significant increase in hepatic markers enzymes (AST &ALT), kidney functions (urea, uric acid and creatinine) lipid profile (T.cholesterol, TG and LDL) concomitant with significant decreases of serum total protein, albumin and HDL level, as well as significant decreases in the number of erythrocytes, platelets and hemoglobin (Hb) levels together with significant increases of leukocytes number. Liver and kidney sections revealed extensive histological changes after IM treatment. On other hand, supplemented diet with S.honey and low dose of Zn (in separated and in combination) led to an obvious improvement of the injured times and ameliorating the damaging effects of IM, which might be due to their antioxidant properties and scavenging abilities against active free radicals. On the other hand, treatment with high dose of Zn, alone or in Combination with S.honey caused an adverse effects on the liver. Hence, further studies are needed to find out the appropriate doses of honey and Zn as antioxidants with fewer side effects.
Keywords: Sider honey; Zinc; lipid profile; liver enzymes; kidney functions; liver and kidney histological observation